La pernice bianca alpina (Lagopus muta helvetica): una sottospecie endemica in declino. Filogeografia, variabilità genetica e aspetti biologici. - Collini, Margherita (2022)
The alpine rock ptarmigan (Lagopus muta helvetica) is considered in the Alps as a relictual glacial species. It is nowadays threaten by global warming, that reduces suitable habitats, and by human disturbance, increasingly frequent at high altitude. On the Pyrenees limited genetic variability was already documented; on the Alps a number of populations display a decreasing census size. We analyzed sequence variation in the mitochondrial DNA D-loop for 148 individuals and ten microsatellite loci for 152 individuals in order to investigate evolutionary history, levels of genetic variability and structure of alpine rock ptarmigan. The samples came from different localities of the Alps. open SCA-178